Analysis of trends in the burden of colorectal cancer in China and globally from 1990 to 2021 with projections for the next 15 years: a cross-sectional study based on the GBD database - Yin, Yulai; Zhang, Xiaoyu (Frontiers in Public Health, 2025)
ObjectiveTo analyze the changes in the burden of colorectal cancer in China and globally from 1990 to 2021, and to explore the disease burden across different age groups and sexes by integrating projected data from 2022 to 2036. This study aims to provide a scientific foundation for formulating targeted prevention and control strategies.Materials and methodsThis study utilized colorectal cancer data from the Global Burden of Disease (GBD) database for the period 1990–2021. Trend analysis was conducted using Joinpoint regression, and future burden projections from 2022 to 2036 were made with an Auto-Regressive Integrated Moving Average (ARIMA) model. Key indicators analyzed included the Age-Standardized Incidence Rate (ASIR), Age-Standardized Prevalence Rate (ASPR), Age-Standardized Mortality Rate (ASMR), and Disability-Adjusted Life Years (DALYs).ResultsBetween 1990 and 2021, the burden of colorectal cancer increased both in China and globally, although notable differences were observed across gender and regions. In Chinese men, the ASIR and ASMR have shown a continuous rise, reaching approximately 50 and 300 per 100,000, respectively, by 2021. Projections indicate that these rates will continue to increase through at least 2036. The ASIR in Chinese women also exhibits an upward trend, whereas the global ASIR for women has declined. From 1990 to 2021, both China and the world experienced a steady rise in ASPR, with minimal fluctuations. In contrast, while the ASDR has decreased in both China and globally, the volatility in China’s ASDR is notably more pronounced than that observed worldwide.ConclusionThe burden of colorectal cancer in China is projected to increase significantly in the coming years, particularly among males and the older adult population. This study provides critical scientific insights for the development of targeted prevention strategies and resource allocation, underscoring the urgent need to enhance early screening initiatives and health education efforts in China.